Metabolically stabilized double-stranded mRNA polyplexes. Issue 7 (October 2018) - Poliskey, Jacob; Crowley, Samuel; Ramanathan, Raghu; White, Christopher; Mathew, Basil; Rice, Kevin
Abstract The metabolic instability of mRNA currently limits its utility for gene therapy. Compared to plasmid DNA, mRNA is significantly more susceptible to digestion by RNase in the circulation following systemic dosing. To increase mRNA metabolic stability, we hybridized a complementary reverse mRNA with forward mRNA to generate double-stranded mRNA (dsmRNA). RNase A digestion of dsmRNA established a 3000-fold improved metabolic stability compared to single-stranded mRNA (ssmRNA). Formulation of a dsmRNA polyplex using a PEG-peptide further improved the stability by 3000-fold. Hydrodynamic dosing and quantitative bioluminescence imaging of luciferase expression in the liver of mice established the potent transfection efficiency of dsmRNA and dsmRNA polyplexes. However, hybridization of the reverse mRNA against the 5′ and 3′ UTR of forward mRNA resulted in UTR denaturation and a tenfold loss in expression. Repeat dosing of dsmRNA polyplexes produced an equivalent transient expression, suggesting the lack of an immune response in mice. Co-administration of excess uncapped dsmRNA with a dsmRNA polyplex failed to knock down expression, suggesting that dsmRNA is not a Dicer substrate. Maximal circulatory stability was achieved using a fully complementary dsmRNA polyplex. The results established dsmRNA as a novel metabolically stable and transfection-competent form of mRNA.